What kind of populism is peronism? - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
After being dormant for several decades, populism has resurfaced in Europe and North America. Since the beginning of the 21st century Europe's populist parties have tripled their vote and were able to put their leaders into government posts in eleven countries, which has increased thirteen fold the population living under populist regimes. The virus has even contaminated Anglo-Saxon countries, which were considered immune. This new strain of populism seems different from the one that infected Latin America for most of the second half of the 20th century. Instead of fostering class struggle it appeals to racism, xenophobia and anti-globalization. In this regard, it has a closer resemblance to early 20th century European populist strains. Although much has been written about populism, a widely accepted definition remains elusive. Before Hugo Chavez burst into the political scene in Venezuela, Argentina's Juan Perón (1895-1974) was considered the quintessential Latin American populist leader. Perón was undoubtedly one of the most successful politicians of the 20th century. Although he entered politics in 1943 Peronism still dominates Argentine politics. Even though it may seem harder to define than populism, its study offers valuable clues about populism's nature and meaning that are relevant today in modern advanced democracies.
Keywords: B00; N14; N16; P40; P47; 330; Peronism; Fascism; Populism; Argentina